2012
DOI: 10.1111/j.1476-5381.2012.02012.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct endothelial pathways underlie sexual dimorphism in vascular auto‐regulation

Abstract: BACKGROUND AND PURPOSEPre-menopausal females have a lower incidence of cardiovascular disease compared with age-matched males, implying differences in the mechanisms and pathways regulating vasoactivity. In small arteries, myogenic tone (constriction in response to raised intraluminal pressure) is a major determinant of vascular resistance. Endothelium-derived dilators, particularly NO, tonically moderate myogenic tone and, because the endothelium is an important target for female sex hormones, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 55 publications
2
32
0
Order By: Relevance
“…As published previously,14, 15 in control female mice without risk factors, EDH was a greater contributor to endothelial‐dependent relaxation than NO (Figure 5A and 5D). When exposed to obesity or hyperlipidemia, female resistance vessels exhibited a significant decline in the EDH component of acetylcholine‐induced relaxation (Figure 5B and 5C).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…As published previously,14, 15 in control female mice without risk factors, EDH was a greater contributor to endothelial‐dependent relaxation than NO (Figure 5A and 5D). When exposed to obesity or hyperlipidemia, female resistance vessels exhibited a significant decline in the EDH component of acetylcholine‐induced relaxation (Figure 5B and 5C).…”
Section: Resultssupporting
confidence: 84%
“…The data reveal profound differences in the effects of cardiometabolic risk factors on the components of endothelial dilation in females versus males. In males (Figure 4), in the absence of risk factors, both eNOS and EDH contribute to vasodilation, with NOS contributing a greater proportion of mesenteric vasodilatory function than EDH (Figure 4A and 4D), consistent with prior studies 14, 15. Exposure of male mice to obesity, with or without hyperlipidemia, resulted in profound impairment in eNOS‐mediated relaxation of resistance vessels.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…30 Tadalafi l, the agent used in the current study, is a phosphodiesterase type 5 inhibitor that enhances NO signaling by impeding the catabolism of cyclic guanosine monophosphate (cGMP), whose downstream eff ects lead to vasorelaxation. In a study by Chan and colleagues, 31 NO-mediated vasodilatation in murine mesenteric arteries exhibited sex-specifi c responses to stimulation of the NO-soluble guanylate cyclase (sGC) pathway. Specifi cally, these investigators found that in male mice, NO-mediated vasodilatation was solely through the NO-sGC-cGMP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This may be likely due to an augmenting effect of female sex hormones on the function of Kcnn3 channels [50].…”
Section: Androgens In Sex-specific Endothelial Dysfunctionmentioning
confidence: 99%